Effect of bias yarn on tensile fracture mechanism of multiaxial 3D angle-interlock woven composites. (February 2021) - Guo, Qiwei; Zhang, Yifan; Li, Diansen; Guo, Ruiqing; Ma, Ming; Chen, Li
Abstract: A novel 3D woven structure was designed and developed in this paper, namely multiaxial 3D angle-interlock woven composites (MAWC). In order to determine the specific influence of bias yarns on the tensile properties and failure mechanisms, two MAWCs with different weave patterns and 3D angle-interlock woven composites (3DAWC) were fabricated. Based on the meso-structure characteristics of MAWC, a realistic meso-model was proposed. The tensile behavior of MAWCs and 3DAWC were experimentally characterized, and the full-field strain distributions were recorded by digital image correlation (DIC). Moreover, a progressive damage model along with the X-ray micro-computed tomography (Micro-CT) technique were applied to reveal the damage processes and failure mechanisms of composites. Results showed that the axial tensile strength of MAWCs decreased due to the change of yarn orientation. The stress-strain curves of two MAWCs presented nonlinear behavior, while those of 3DAWC could be seen as linear within the whole strain range. Stress concentration regions of two MAWCs were found to be distributed more dispersedly than those of 3DAWC. The local tow splitting, fiber slippage and interfacial debonding were the primary failure modes of bias yarn in MAWCs under tension. Graphical abstract: Image 1 Highlights: A novel multiaxial 3D woven configuration containing bias yarn is designed and presented. A realistic meso-model is proposed based on the meso-structure characteristics of MAWC. Tensile tests are conducted to determine the specific effect of bias yarn on the mechanical property. A progressive damage model is implemented to reveal the fracture mechanism of MAWC.